European record of Subramaniula thielavioides on opium poppy - Martin Pastirčák; Katarína Pastirčáková (Acta Mycologica, 2013)
In the course of a study of fungal biodiversity of opium poppy (Papaver somniferum) plants collected in production area of Slovakia, an ascomycete belonging to the genus Subramaniula was isolated. The fungus identified as Subramaniula thielavioides has been reported for the first time from Slovakia. This record also represents the first European locality. Brief morphological description of the fungus based on an isolate from flower petals of opium poppy is provided.